The impact of health literacy on quality of life in patients with chronic diseases - Zhang, Jiali; Chen, Yinhai; Lu, Yuanwei; Jiang, Xuan; Lin, Congxuan; Ke, Xiong (Frontiers in Public Health, 2025)
ObjectiveWe aimed to assess quality of life in patients with chronic diseases and identify influencing factors, as well as to explore the relationship between health literacy and quality of life in this population.MethodsWe used health literacy and EuroQol 5-Dimensions 5-Level version survey data from chronically ill patients in the 2023 Sichuan Province Chinese Resident Psychological and Behavioral Survey Study. We analyzed factors influencing quality of life using a tobit regression model and examined the relationship between quality of life and health literacy using canonical correlation analysis.ResultsThe health utility value for quality of life among 611 patients with chronic diseases was 0.95 (0.86–1), with an EuroQol Visual Analog Scale score of 71.04 ± 16.21. Regression analysis revealed that health literacy (p = 0.004), sex (p = 0.015), body mass index (p = 0.047), occupation (p = 0.012), marital status (p = 0.026), debt status (p = 0.001), comorbidity (p < 0.001) and living alone (p = 0.033) were significantly associated with quality of life. Canonical correlation analysis showed a correlation of 0.269 (p < 0.001) between health literacy and quality of life, primarily related to factors such as treatment information, mental health, and vaccine type, which were correlated with pain or discomfort.ConclusionEnhancing health literacy can positively impact the life quality of patients with chronic diseases. Key elements of health literacy interventions should include evaluating treatment information, accessing resources to address mental health concerns, and determining individual vaccine needs. Health education strategies should be developed to improve both health literacy and quality of life for patients with chronic diseases.